3D MODELING OF COMBUSTION THERMOCHEMICAL ACTIVATED FUEL - Askarova Aliya; Bolegenova Saltanat; Safarik Pavel; Maximov Valeriy; Bolegenova Symbat; Nugymanova Aizhan (Academic Scientific Journal of Computer Science, 2019)
This article presents the results of numerical research of plasma thermochemical processes of preparing solid fuels for combustion in combustion chambers. During the numerical experiments have been applied the newest information technology and method of 3-D computer modeling of heat and mass transfer in the furnace space. Received the basic laws of convective heat and mass transfer in turbulent flows in the presence of chemical reactions using modern numerical methods, giving a complete description of the complex processes occurring in a real combustion chamber. Research of three-dimensional temperature and concentration fields has allowed establishing laws of the development of the combustion process in the entire volume of the object under study. Satisfactory agreement is obtained estimates with known results of natural experiments. Authors of article for the first time investigate influence of plasma thermochemical treatment of pulverized coal flows on the main characteristics of the physicochemical processes of solid fuel combustion. It has been established that the method of thermochemical activation of pulverized coal flows makes it possible to significantly optimize the process of burning low-grade high-ash Kazakhstan coal in the combustion chambers of the thermal power plants of Kazakhstan, significantly reduce emissions of harmful substances into the environment and create a way to obtain "clean" energy on energy facilities.